Membangun Kembali Nilai-Nilai Dasar Keislaman sebagai Resolusi Konflik Ahmadiyah: Diskursus Hak Kebebasan Beragama dan Berkeyakinan - Dedi Putra (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Justice, tolerance, and mutual forgiveness is the fundamental values of Islam. The principle must be understood and imitated and realized in social attitudes. But in fact, the principle of nonviolence and peace in Islam was limited to the principle of not integral to the individual Muslim. This has often resulted in various conflicts in society. This paper focuses existence of Ahmadiyah conflict. Ahmadiyah position as a minority group should get protection from the state. The State must ensure and protect the rights of religious freedom which is owned by Ahmadiyah. So with the protection provided by the state, the new state acts can be said to be in accordance with the constitutional mandate